The Influence of Contextual Cue on Antinociceptive Tolerance and Facilitation of Memory With Morphine - Mototaka Nakama-Kitamura; Nobutaka Doe (Elsevier, 2003)
The response latencies of the biting response in the tail-pinch test and step-through response in the passive avoidance test were measured in mice. 1) Scopolamine decreased the latency of the step-through response in the passive avoidance test, but diazepam did not. 2) Morphine (5 mg/kg, i.p.) was given 30 min before the test for 4 consecutive days in novel environments by sessions. The decrease in biting response latency was attenuated and delayed in the groups in which contexts were changed daily compared to the groups that were maintained in the same context throughout the conditioning period. The latency of step-through response was increased with morphine in both groups regardless of the change or lack of change in context. 3) Morphine was repeatedly administered to animals in the same environment and then the context was changed. The decreased latency in the tail-pinch test was significantly reversed by the change in context, but the response in the passive avoidance test maintained a longer latency. These findings indicate that morphine develops associative and nonassociative antinociceptive tolerance, indicating that antinociceptive tolerance to morphine has contextual specificity, but the facilitation of memory does not. The results indicate that the facilitation of memory with morphine may contribute to associative learning in antinociceptive tolerance to morphine.